Faktor-faktor Determinan Pemberdayaan Wanita dalam Pengelolaan Limbah Rumah Tangga Berkelanjutan - Hasan Ibrahim (Partner, 2020)
In Jorong Podang Rontang Nagari Koto Tuo, Limapuluh Regency, West Sumatra City, the number of underprivileged households is relatively high, 72 households. 98% of the members of the women farmer groups are cultivating farmers with 0.1-0.2 ha of arable land so that they are categorized as small farmers. The behavior of household waste management by women farmer groups is generally not sustainable because they dispose of it behind the house and allow it to rot. The method used is a survey method. Qualitative data and information were analyzed using qualitative analysis methods through a process of coding, categorization, interpretation, meaning, and abstraction. Then the data will be analyzed with the SPSS program. Based on the analysis results obtained by the equation: Y = 12,860 + 0.021X1 - 0.47X2 - 0.78X3. The equation shows that there is a positive relationship between the empowerment of women peasants and the knowledge of women peasants. In contrast, the motivation of women farmers, local wisdom and the empowerment of women farmers has a negative relationship. Positive and negative influences between independent variables (knowledge of women farmers, motivation of women farmers and local wisdom) and dependent variables (empowerment of women farmers) are not necessarily interpreted mathematically, but interpretation must be within the framework of empowerment as a reflection of women's emancipation, collective community participation in carrying out development, as well as community involvement (women) in participating in carrying out development. The influence of these independent factors is a leverage for women's empowerment to be independent in sustainable waste management. Keywords: Waste, Empowerment, Women Farmers, Nagari, Local Wisdom